Pengetahuan Gizi Ibu dan Status Gizi Balita di Posyandu Tanjung Jaya - Aline Wijaya, Maretha; Frisca Frisca (Jurnal Ilmiah Kedokteran dan Kesehatan, 2025)
Nutritional problems among toddlers remain a public health issue in Indonesia, including in the Central Lampung region. A mother’s knowledge, as the primary caregiver, plays a crucial role in determining a child’s nutritional status. Good knowledge can help mothers provide balanced nutrition for their children. This study aimed to determine the relationship between mothers’ knowledge of toddler nutrition and the nutritional status of toddlers at Posyandu Tanjung Jaya, Bangun Rejo Subdistrict, Central Lampung. This research used an analytic design with a cross-sectional approach and was conducted from January to February 2024. The respondents were 75 mothers with children aged 1–5 years who visited Posyandu Tanjung Jaya. Mothers’nutritional knowledge was collected through questionnaires, while data on children’s nutritional status were obtained from Posyandu records. Analysis was performed using Fisher’s Exact Test. The results showed that most mothers (93.8%) had good nutritional knowledge, and 94.7% of them had children with good nutritional status. Statistical analysis showed a significant relationship between maternal knowledge and toddler nutritional status (p < 0.001; PR = 11.29). Mothers with good knowledge were 11 times more likely to have well-nourished children. These findings highlight the importance of continuous nutrition education as a preventive effort against toddler malnutrition.